2021
DOI: 10.1016/j.arthro.2020.12.198
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Reach Over the Top and Preserve the Hip Labrum

Abstract: There is increasing interest in fine tuning of hip arthroscopy to improve the long-term outcomes of femoroacetabular impingement (FAI) surgery. Recently, some advocated for rim trimming and labral refixation without taking down the labrum, using a so-called over-the-top technique. Although some studies have already reported on the outcomes of this procedure, very few have focused on how maintaining an unharmed chondrolabral junction may decrease cartilage wear over time. Preserving labral attachment should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The acetabular labrum can enhance the distractive stability of the hip, prevent supraphysiologic distraction of the hip and regulate synovial fluid circulation 26–28 . Suppauksorn et al found that labral reconstruction could result in loss of suction seal, 29 while Slullitel et al thought that maintenance of the chondrolabral union can protect the function of suction seal and help improve stability, load distribution, and regulation of the synovial fluid 30 . In the low resection depth group, the labrum was not completely detached, leaving the labrum and cartilage junction, which could maintain the role of the suction seal of the acetabular labrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acetabular labrum can enhance the distractive stability of the hip, prevent supraphysiologic distraction of the hip and regulate synovial fluid circulation 26–28 . Suppauksorn et al found that labral reconstruction could result in loss of suction seal, 29 while Slullitel et al thought that maintenance of the chondrolabral union can protect the function of suction seal and help improve stability, load distribution, and regulation of the synovial fluid 30 . In the low resection depth group, the labrum was not completely detached, leaving the labrum and cartilage junction, which could maintain the role of the suction seal of the acetabular labrum.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Suppauksorn et al found that labral reconstruction could result in loss of suction seal, 29 while Slullitel et al thought that maintenance of the chondrolabral union can protect the function of suction seal and help improve stability, load distribution, and regulation of the synovial fluid. 30 In the low resection depth group, the labrum was not completely detached, leaving the labrum and cartilage junction, which could maintain the role of the suction seal of the acetabular labrum. In comparison with the low resection depth group, the acetabulum in the high resection depth group was removed more and it must be completely detached from the acetabular rim during the operation.…”
Section: Potential Biomechanical Explanations For Excessive Resectionmentioning
confidence: 94%